New and future developments in microbial biotechnology and bioengineering : sustainable agriculture. - Singh, H. B., Dr; Vaishnav, Anukool (Elsevier, 2022)
New and Future Developments in Microbial Biotechnology and Bioengineering: Sustainable Agriculture: Revitalization through Organic Products provides a comprehensive overview of different organic products which work as plant biostimulants, i.e., protein hydrolysates, chitosan, microbial derived exopolysaccharides, pectin, nanoparticles, etc. In addition, detailed insights in their mechanisms for plant growth promotion and stress alleviation are covered. This volume further discusses the extraction and formulation of organic products for use in sustainable agriculture. The application of microbial derived secondary metabolites in crop protection is also extensively covered. This book will be ideal for agrochemists, biotechnologists, biochemists, industrialists, researchers and scientists working on organic farming.